PELAKSANAAN PEMILIHAN PENGADAAN BAHAN PUSTAKA DI PERPUSTAKAAN MADRASAH ALIYAH NEGERI 3 PALEMBANG - Annur, Saipul; Ibrahim, Ibrahim; Salsabila, Siti Husna (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This study discusses "Implementation of Selection of Library Materials Procurement in the Library of Madrasah Aliyah Negeri 3 Palembang". The purpose of this study is to describe how the implementation of the selection of procurement of library materials in the library of Madrasah Aliyah Negeri 3 Palembang and to analyze the factors that influence the implementation of the selection of procurement of library materials in the library of Madrasah Aliyah Negeri 3 Palembang. The researcher used a qualitative approach with a descriptive type, and the main informants in this study were the head of the library and library staff. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. Test the validity of research data by source triangulation, technical triangulation and time triangulation. This research was conducted on May 17 – July 3, 2023. The research results obtained by researchers indicated that the implementation of the selection of procurement of library materials in the Palembang 3 Madrasah Aliyah Library is carried out once a year according to user needs. The supporting factors are human resources and infrastructure in the library, while the inhibiting factor is limited funds.Keywords: Implementation, Selection, Library Materials